The ignition fragment wood heated to a high temperature of the plate; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Zakharevich A. V. Arkadiy Vladimirovich (2015, 2015)
Title screen